Mendeley: International Food Policy Research Institute (IFPRI) Case Study - Mendeley-Elsevier (Elsevier, 2014)
The research conducted at the IFPRI is essential to advancing its mission of a hunger, malnutrition, and poverty free world. Furthermore, the complexity of the challenges and the global impact of the institute’s work require the timely organization and dissemination of information. This can only be achieved in a dynamic forum that cultivates the transfer of knowledge and facilitates engagement and exchange among stakeholders.